ISOTOPIC COMPOSITION OF THE HERCYNIAN CRUST OF SOUTHERN MONGOLIA: SUBSTANTIATION OF THE HERCYNIAN JUVENILE CRUST-FORMING EVENT - Yarmolyuk V.V.; Kovalenko V.I.; Kovach V.P.; Terent'Eva L.B.; Kozakov I.K.; Kotov A.B.; Eenjin G. (My University, 2007)
Geochronological and Nd isotopic studies of Phanerozoic granitoids of the Central Asian foldbelt (CAFB), as well as Phanerozoic folded structures of the Cordilleras and Appalachians of North America and eastern Australia, made it possible to distinguish the Phanerozoic stage in the formation of the juvenile continental crust. Recognition of this stage essentially changed the notion on the evolution and growth rate of the continental crust in the geological history. In particular, this fact revealed the necessity to study stages, sources, and leading mechanisms of the juvenile crust formation in the Late Precambrian and Phanerozoic. For example, the results of our studies made it possible to distinguish the Riphean, Caledonian, Hercynian, and Indosinian cycles of crust formation in the Phanerozoic of the CAFB. These cycles were marked by the formation of the respective Nd isotopic crustal provinces.